The relationship between affective disorders and hormonal and metabolic parameters in women with polycystic ovary syndrome - (:unkn) unknown (My University, 2013)
Amaç: Polikistik over sendromlu (PKOS) hastalarda afektif bozukluklar ile hormonal ve biyokimyasal paramet- reler arasındaki ilişkiyi anlamak. Yöntemler: PKOS tanısı almış 15 hasta, yaş ve vücut kitle endeksi benzer olan kontrol grubuyla (n=19) karşı- laştırıldı. Beck Depresyon Ölçeği ve Durumluk-Sürekli Anksiyete Ölçeği kullanılarak anksiyete ve depresyon semptomları sorgulandı. Bulgular: Polikistik over sendromlu hastaların depres- yon ve anksiyete skorları serbest testosterone seviyeleri ile korele idi. Anksiyete skorları HDL ve kardiyovasküler hastalıklar için bağımsız bir risk faktörü olarak kabul edi- len lipoprotein-a ile koreleydi. Kontrol grubunda anksiyete skorları interlökin 1beta ile koreleydi. Sonuç: Polikistik over sendromlu hastalarda androjenler ve afektif bozukluklar arasında bağlantı vardır. Lipopro- tein-a ve anksiyete skorları arasındaki korelasyon afek- tif bozukluklar ve kardiyovasküler hastalıklar arasındaki bağ olabilir. Polikistik over sendromlu kadınlarda afektif bozuklukların patofizylojisinde farklı bir mekanizma rol oynayabilir.

Objective: To understand the relationship among affec- tive disorders and hormonal and biochemical parameters in women with polycystic ovary syndrome (PCOS). Methods: Women with PCOS (n=15) were compared to body mass index and age matched control group (n=19). Beck Depression Inventory and Stait Trait Anxiety Inven- tory were used to assess the presence of depression and anxiety symptoms. Results: Depression and anxiety scores of women with PCOS correlated with free testosterone levels. Their anxi- ety scores correlated with HDL and lipoprotein-a (Lp-a), an independent marker for increased cardiovascular dis- ease. In the control group anxiety score correlated with interleukin-1β. Conclusion: There was a relationship between increased androgens and affective disorders in women with PCOS. The correlation between Lp-a and anxiety scores may be the link between affective disorders and cardiovas- cular diseases. A different mechanism may play role in the pathophysiology of affective disorders in women with PCOS.
Polikistik over sendromlu kadınlarda afektif bozukluklar ile hormonal ve metabolik parametreler arasındaki ilişki
Keywords: Cerrahi